MARITIME DIPLOMACY SEBAGAI STRATEGI PEMBANGUNAN KEAMANAN MARITIM INDONESIA - Nugraha, Muhammad Harry Riana; Sudirman, Arfin (JWP (Jurnal Wacana Politik), 2016)
Indonesiaâs geographical conditions that sourrounded by ocean should be considered as an added value for maritime diplomacy for the sake of the development of Indonesia. Therefore, in terms of geoculture, Maritime Diplomacy should be taken into account as one of the main pillars to build maritime security in Indonesia including the use of maritime diplomacy in response to security threats, so that the defense capabilities will be gradually improved. This article will examine the importance of organizing Indonesiaâs maritime sector regarding the vision of the Global Maritime Fulcrum (GMF) in order to see the strengths and weaknesses of Indonesian Navyâs capabilities as an instrument of Indonesiaâs Maritime diplomacy to support the development of maritime security. This article also argued that the most important in Indonesiaâs Maritime Diplomacy is that Indonesia is capable to guarantee maritime security for all stakeholders regionally and globally. Indonesia needs to improve management and expand promotion for all trading ports available, namely Jakarta and Surabaya as well as other ports as a hub of global maritime prospects. By enhancing maritime safety and security, various international cooperation will be maintained and pro table for Indonesia.Â